2008
DOI: 10.1074/jbc.m708588200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Ser357 of Rat Insulin Receptor Substrate-1 Mediates Adverse Effects of Protein Kinase C-δ on Insulin Action in Skeletal Muscle Cells

Abstract: The activation of the protein kinase C (PKC) family of serine/ threonine kinases contributes to the modulation of insulin signaling, and the PKC-dependent phosphorylation of insulin receptor substrate (IRS)-1 has been implicated in the development of insulin resistance. Here we demonstrate Ser 357 of rat IRS-1 as a novel PKC-␦-dependent phosphorylation site in skeletal muscle cells upon stimulation with insulin and phorbol ester using Ser(P) 357 antibodies and active and kinase dead mutants of PKC-␦. Phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 50 publications
2
20
0
Order By: Relevance
“…The results regarding PKCd-mediated serine phosphorylation of IRS-1 agree with recent studies indicating that this isoform may also be involved in negative regulation of IRS-1, several putative serine sites having been identified (Greene et al 2004, Waraich et al 2008. Phosphorylation of IRS-1 Ser 307 in the cells expressing the different chimeras appears to support findings in recent studies showing that this serine residue may be a target for insulin-activated PKC isoforms, although in CHO-IR cells Ser24 is also specifically implicated.…”
Section: Discussionsupporting
confidence: 81%
“…The results regarding PKCd-mediated serine phosphorylation of IRS-1 agree with recent studies indicating that this isoform may also be involved in negative regulation of IRS-1, several putative serine sites having been identified (Greene et al 2004, Waraich et al 2008. Phosphorylation of IRS-1 Ser 307 in the cells expressing the different chimeras appears to support findings in recent studies showing that this serine residue may be a target for insulin-activated PKC isoforms, although in CHO-IR cells Ser24 is also specifically implicated.…”
Section: Discussionsupporting
confidence: 81%
“…While PKCδ has also been implicated in the inhibition of insulin signal transduction through serine phosphorylation of IRS-1 [9], our findings suggest an effect of the kinase on lipogenesis, especially in the liver, which may indirectly influence insulin sensitivity. This could be through subtle effects on insulin signalling which we were unable to detect in tissues from mice injected with a maximal bolus of insulin.…”
Section: Discussionmentioning
confidence: 71%
“…PKC has been reported to phosphorylate serine 307/IRS1, followed by a decrease in its tyrosine phosphorylation in skeletal muscle and muscular insulin resistance (23). Furthermore, Ser-24, -318, -357, and -1101 of IRS1 have all been reported to be phosphorylated by PKC (15)(16)(17)(18)(19)(20)31). However, PMA did not increase the phosphorylation of these sites on IRS1 in endothelial cells.…”
Section: Discussionmentioning
confidence: 89%
“…Multiple reports have shown that PKC activation can increase serine/threonine phosphorylation of IR and IRS1/2 and decrease their levels of tyrosine phosphorylation and functions induced by insulin (15)(16)(17)(18)(19)(20)31). Conventional and novel PKC␣/␤/␦/⑀ and -isoforms, activated by diacylglycerol, due to hyperlipidemia or hyperglycemia (19), have been reported to cause insulin resistance (15)(16)(17)(18)(19)(20)31) mainly in liver, muscle, or adipose tissue where there is an increase in threonine/serine phosphorylation of IR or IRS. A, BAECs were treated with or without PMA and followed by stimulation of VEGF after transfection with p85 siRNA and/or p85 pro-1 deletion mutant.…”
Section: Discussionmentioning
confidence: 99%